The Effect of Three Months Regular Aerobic Exercise on Premenstrual Syndrome - Zinat Ghanbari; Farideh Dehghan Manshavi; Mina Jafarabadi (Tehran University of Medical Sciences, 2008)
Objective: To determine the effects of three-month regular aerobic exercise on the PMS symptoms. Also correlations with age, education, marital status and severity of PMS symptoms were studied. Materials and Methods: A Quasi- Experimental study was conducted on 91 volunteer women with regular menstrual cycle and no history of gynecological, endocrinological and psychological disorders. The study was done during March 2005- March 2007, in Tehran University of Medical Sciences. A Modified Menstrual Distress Questionnaire (MMDQ) was used in this study. Participants were divided into two groups: Non-exercised, they also didn't have any past experience of regular exercise (n= 48) and Exercised (n= 43). The exercise time duration was one hour and was carried out three times per week for three months.  Emotional, behavioral, electrolyte, autonomic, neurovegatative and skin symptoms of PMS were compared between two groups. P value was considered significant at < 0.05. Results: A significant difference was observed for electrolytic, neurovegetative and cognitive symptoms before and after the exercise. Also the severity of skin and neurovegetative symptoms were different in experimental groups with and without past history of doing regular exercise. There was no correlation between age, education, marital status and severity of PMS symptoms. Conclusion: Three months of regular aerobic exercise effectively reduces the severity of PMS symptoms.